Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the given differential equation [tex]\(\cot(x) \, dx + \frac{e^y}{e^y + 1} \, dy = 0\)[/tex], let's follow these steps:
1. Rearrange the given equation:
[tex]\[ \cot(x) \, dx + \frac{e^y}{e^y + 1} \, dy = 0 \][/tex]
2. Separate the variables:
[tex]\[ \cot(x) \, dx = -\frac{e^y}{e^y + 1} \, dy \][/tex]
3. Integrate both sides:
[tex]\[ \int \cot(x) \, dx = - \int \frac{e^y}{e^y + 1} \, dy \][/tex]
4. Compute the integral on the left-hand side:
The integral of [tex]\(\cot(x)\)[/tex] with respect to [tex]\(x\)[/tex] is:
[tex]\[ \int \cot(x) \, dx = \ln|\sin(x)| \][/tex]
5. Compute the integral on the right-hand side:
To integrate [tex]\(- \int \frac{e^y}{e^y + 1} \, dy\)[/tex], we can use the substitution [tex]\(u = e^y + 1\)[/tex]. Notice that [tex]\(du = e^y \, dy\)[/tex], thus:
[tex]\[ \int \frac{e^y}{e^y + 1} \, dy = \int \frac{1}{u} \, du = \ln|u| \][/tex]
Substituting [tex]\(u\)[/tex] back, we get:
[tex]\[ - \int \frac{e^y}{e^y + 1} \, dy = - \ln|e^y + 1| \][/tex]
6. Combine the results of both integrals:
[tex]\[ \ln|\sin(x)| = - \ln|e^y + 1| + C \][/tex]
where [tex]\(C\)[/tex] is the constant of integration.
7. Simplify the equation:
Combine the logarithmic terms on one side:
[tex]\[ \ln|\sin(x)| + \ln|e^y + 1| = C \][/tex]
Using the property of logarithms [tex]\(\ln(a) + \ln(b) = \ln(ab)\)[/tex]:
[tex]\[ \ln|\sin(x) \cdot (e^y + 1)| = C \][/tex]
Exponentiating both sides to eliminate the logarithm, we get:
[tex]\[ |\sin(x) \cdot (e^y + 1)| = e^C \][/tex]
Let [tex]\(e^C = C'\)[/tex], where [tex]\(C'\)[/tex] is a new constant. Thus:
[tex]\[ \sin(x) \cdot (e^y + 1) = C' \][/tex]
8. Final result:
[tex]\[ C' = \sin(x) \cdot (e^y + 1) \][/tex]
1. Rearrange the given equation:
[tex]\[ \cot(x) \, dx + \frac{e^y}{e^y + 1} \, dy = 0 \][/tex]
2. Separate the variables:
[tex]\[ \cot(x) \, dx = -\frac{e^y}{e^y + 1} \, dy \][/tex]
3. Integrate both sides:
[tex]\[ \int \cot(x) \, dx = - \int \frac{e^y}{e^y + 1} \, dy \][/tex]
4. Compute the integral on the left-hand side:
The integral of [tex]\(\cot(x)\)[/tex] with respect to [tex]\(x\)[/tex] is:
[tex]\[ \int \cot(x) \, dx = \ln|\sin(x)| \][/tex]
5. Compute the integral on the right-hand side:
To integrate [tex]\(- \int \frac{e^y}{e^y + 1} \, dy\)[/tex], we can use the substitution [tex]\(u = e^y + 1\)[/tex]. Notice that [tex]\(du = e^y \, dy\)[/tex], thus:
[tex]\[ \int \frac{e^y}{e^y + 1} \, dy = \int \frac{1}{u} \, du = \ln|u| \][/tex]
Substituting [tex]\(u\)[/tex] back, we get:
[tex]\[ - \int \frac{e^y}{e^y + 1} \, dy = - \ln|e^y + 1| \][/tex]
6. Combine the results of both integrals:
[tex]\[ \ln|\sin(x)| = - \ln|e^y + 1| + C \][/tex]
where [tex]\(C\)[/tex] is the constant of integration.
7. Simplify the equation:
Combine the logarithmic terms on one side:
[tex]\[ \ln|\sin(x)| + \ln|e^y + 1| = C \][/tex]
Using the property of logarithms [tex]\(\ln(a) + \ln(b) = \ln(ab)\)[/tex]:
[tex]\[ \ln|\sin(x) \cdot (e^y + 1)| = C \][/tex]
Exponentiating both sides to eliminate the logarithm, we get:
[tex]\[ |\sin(x) \cdot (e^y + 1)| = e^C \][/tex]
Let [tex]\(e^C = C'\)[/tex], where [tex]\(C'\)[/tex] is a new constant. Thus:
[tex]\[ \sin(x) \cdot (e^y + 1) = C' \][/tex]
8. Final result:
[tex]\[ C' = \sin(x) \cdot (e^y + 1) \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.